Preparation of Spent Hen Meat Pickle with Gooseberry Powder - Kumaresan, S.; Pal, U.K.; Mandal , P.K.; Kasthuri, S. (Journal of Meat Science, 2019)
The present study was conducted to standardize the recipe for preparation of spent hen meat pickle using gooseberry powder with reduced levels of vegetable oil and acetic acid and to evaluate the effect of gooseberry powder on sensory quality of spent hen meat pickle. A pickle recipe was standardized containing 10% onion, ginger and garlic paste, 15% oil, 15% meat broth to produce acceptable quality spent hen meat pickle. To select suitable levels 1, 2 and 3% gooseberry powder (GBP) was incorporated along with 0.5% acetic acid. Based on the experimental results, it was observed that spent hen meat pickle containing 2 and 3% GBP had comparatively lower pH (4.34±0.1 to 4.48±0.1) and better overall acceptability scores (7.20±0.1 to 7.33±0.1) when compared to product containing 1% GBP.